Med lätt bagage: Om köpstopp, utrensning och hållbar konsumtion - Fredriksson, Cecilia (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2016)
In the wake of welfare, a number of alternative consumption practices have emerged. Meeting the obligations of the consumer society is an ambivalent practice with moral implications that contain strong elements of both freedom of choice and regulation. Alternative consumer practices is following that discourse and together with the growing interest in ethics and environment, the individual is expected to realize him- or herself through creative, green and sustainable consumption. Recycling and second-hand are important drivers of these processes. Practices of creative self-expression are related to specific considerations and confessions in the context of positioning in consumer society. Taking a starting point in “Shop-stop” or “Stop-buying-acts” as a cultural theme, this article focus on crafting confessions and creativity. By thematising a number of cultural programmes of action, it is my intention to shed light on how these programmes of action have become an important part of how alternative consumption trends acts as self-regulating practices.